The verb phrase in English : investigating recent language change with corpora - Aarts, Bas, 1961- (New York : Cambridge University Press, 2012)
'The chapters in this volume feature new and groundbreaking research carried out by leading scholars and promising young researchers from around the world on recent changes in the English verb phrase. Drawing on authentic corpus data, the papers consider both spoken and written English in several genres. Each contribution pays particular attention to the methodologies used for investigating short-term patterns of change in English, with detailed discussions of controversies in this area. This cutting-edge collection is essential reading for historians of the English language, syntacticians and corpus linguists'--
Includes bibliographical references (p. 405-435) and indexes.
Keywords: English language -- Verb phrase; English language -- Syntax; Linguistic change